2023
DOI: 10.3390/jcm12030976
|View full text |Cite
|
Sign up to set email alerts
|

Salivary Human β-Defensin 1-3 and Human α-Defensin-1 Levels in Relation to the Extent of Periodontal Disease and Tooth Loss in the Elderly

Abstract: The oral innate immune response may diminish with aging. In the present study, the aim was to examine human β-defensin (hBD) 1-3 and human neutrophil peptide (HNP)-1 levels in the saliva of an elderly population to establish the extent of periodontal disease and tooth loss. A total of 175 individuals aged ≥ 65 years were divided into five groups based on the number of teeth with a pocket depth ≥ 4 mm as follows: 17 pocket-free individuals (Control), 55 individuals having 1–6 pocket teeth (PerioA), 33 individua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…hBDs can also neutralize the lipopolysaccharide on the membrane of the gram-negative bacteria. 9 On the contrary, bacteria resist by changing their cell envelope structure, nesting in biofilms, cleaving the hBDs, or inhibiting their expression pathways. 23 , 24 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…hBDs can also neutralize the lipopolysaccharide on the membrane of the gram-negative bacteria. 9 On the contrary, bacteria resist by changing their cell envelope structure, nesting in biofilms, cleaving the hBDs, or inhibiting their expression pathways. 23 , 24 …”
Section: Discussionmentioning
confidence: 99%
“…Based on genomic targeting, the hBD family includes more than 20 defensins, of which types 1 to 4 are expressed in the gingival epithelium. 4 , 9 According to the literature, hBD-1 has a broader range of antimicrobial activity than the other hBDs, and it is effective against both gram-negative and gram-positive bacteria. 10 Unlike hBD-2 and -3 expression, which depends on bacterial stimulation, hBD-1 has a continuous expression in saliva and gingival crevicular fluid (GCF), 11 and thus could be considered the frontline of immune system defense when encountered pathogens.…”
Section: Introductionmentioning
confidence: 99%
“…Alterations in salivary neutrophil defensin levels have been associated with oral diseases such as squamous cell carcinoma, lichen planus, glossitis associated with iron deficiency, and mandibular osteomyelitis [102][103][104]. Regarding periodontitis, recent studies have found that the levels of neutrophil defensins in SWS increased progressively with rising numbers of pocketed teeth, which can be observed in both the adult population aged between 40-60 years [105] and the elderly population aged 65 years or more [106]. The consistent elevation of salivary neutrophil defensin in patients with CP suggests its potential utility as a biomarker for periodontitis diagnosis [107].…”
Section: Discussionmentioning
confidence: 99%
“…Jurczak et al (2015) indicated a significant relationship between early childhood caries and salivary hBD-2 levels, and they recommended this antimicrobial peptide as a potential disease progression biomarker [ 92 ]. Finally, age may act as a confounding factor in the relation between oral hBD levels and the extent of periodontal destruction [ 93 ].…”
Section: Immune Response Regulation In Head and Neck Cancersmentioning
confidence: 99%